Ritual Hape Kleru Gaka Kaju di Desa Tapobali Lembata sebagai Pewarisan Pendidikan Nilai bagi Peserta Didik - Bala, Alexander; Butun, Yuvenalis; Genua, Veronika; Larasati, Maria Marietta Bali; Demon, Yosef (Balai Bahasa Provinsi Bali, 2024)
Each ethnic group has local wisdom in interpreting cultural events in their environment. This article discusses the kleru gaka kaju hape ritual in the Wolowutun community, Tapobali Village, Wulandoni, Lembata, East Nusa Tenggara. This ritual is a ceremony of thanksgiving for harvesting Swallow nests. Hape kleru gaka kaju means biting a hanging betel nut. The research problem, namely the means used, the participants involved, the stages of implementation, and the educational values in it. The purpose of his research is to explain the means, participants, stages, and values in the hape klru gaka kaju ritual. The research design uses a qualitative design. Data collection techniques, including observation and interview techniques. Data analysis includes identification, classification, and interpretation of data. The findings of the study indicated that the ingredients used included coal fire, kitchen ashes, coconut shells, agarwood, ginger, cotton fiber, baby corn, areca nut, betel nut, titi corn, coconut shells, red chicken, chicken eggs, brown rice, mayang. coconut, roped bamboo, shell glass, palm sap, plates made of pumpkin, coconut shell spoon; the participants involved were the eldest, youngest, traditional house keepers, tara mortal envoys, representatives of the Tobil tribe and residents present; the implementation includes the stages of picking up ancestral spirits, the stages of hanging areca nuts on wood, the stages of collecting offerings, the stages of receiving blessed water, the stages of sweeping and cleaning the remnants of the tools used; and contain religious values, ecological, nationalism, love for the motherland. AbstrakSetiap etnik memiliki kearifan lokal dalam memaknai peristiwa budaya yang ada dalam lingkungannya. Artikel ini membahas tentang ritual hape kleru gaka kaju dalam masyarakat Wolowutun, Desa Tapobali, Wulandoni, Lembata, Nusa Tenggara Timur. Ritual ini merupakan seremonial syukur atas panen sarang Walet. Hape kleru gaka kaju berarti menggigit pinang yang digantung. Masalah penelitiannya, yakni sarana yang digunakan, partisipan yang terlibat, tahapan pelaksanaan, dan nilai-nilai pendidikan di dalamnya. Tujuan penelitiannya untuk menjelaskan tentang sarana, partisipan, tahapan, dan nilai-nilai dalam ritual hape kleru gaka kaju. Desain penelitiannya menggunakan desain kualitatif. Teknik pengumpulan data, meliputi teknik observasi dan wawancara. Analisis data meliputi identifikasi, klasifikasi, dan interpretasi data. Temuan penelitian menunjukkan bahwa sarana yang digunakan, antara lain bara api, abu dapur, tempurung kelapa, kayu gaharu, jahe, serat kapas, jagung muda, pinang, sirih, jagung titi, kukuran kelapa, ayam merah, telur ayam, beras merah, mayang kelapa, bambu bertali, gelas tempurung, nira lontar, piring dari buah labu, senduk tempurung kelapa; partisipan yang terlibat adalah sulung, bungsu, penjaga rumah adat, utusan tara fana, perwakilan suku Tobil dan warga yang hadir; pelaksanaan meliputi tahapan penjemputan arwah leluhur, tahapan menggantung pinang di kayu, tahapan mengumpulkan sesajian, tahapan menerima air berkat, tahapan menyapu dan membersihkan sisa-sisa sarana yang digunakan; dan mengandung nilai-nilai religius, ekologis, nasionalisme, cinta tanah air.